Blockchain for the circular economy: Theorizing blockchain's role in the transition to a circular economy through an empirical investigation. (15th March 2022) - Böhmecke‐Schwafert, Moritz; Wehinger, Marie; Teigland, Robin
Abstract: Blockchain is increasingly lauded as an enabler of the transition to a circular economy. While there is considerable conceptual research and some empirical studies on this phenomenon, scholars have yet to develop a theoretical model of blockchain's role in this transition. Grounded in the sustainability transition literature, this paper addresses this gap through the following research question: What role does blockchain play in the transition to a circular economy? Following an abductive approach, we conducted interviews with ground‐level experts implementing blockchain innovations for the circular economy across Europe and the United States. Through a thematic analysis, we derived a theoretical model of the relationships among (1) drivers and barriers of the transition to a circular economy, (2) blockchain innovation for the circular economy, (3) technical challenges of blockchain, and (4) the circular economy. While blockchain plays a moderating role, interviewees considered it only an infrastructural resource rather than a panacea.